Enhancing digital literacy: Developing powerpoint-based augmented reality media integrated with socioscientific issues - Maulidah, Lailatul; Hariyadi, Slamet; Fikri, Kamalia; Buroidah, Hikmah; Siswati, Bea Hana; Anwar, Muhamad Khoirul; Wahono, Bevo; Suratno (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2026)
Preliminary observations indicated that students in Islamic senior high schools located in agro-industrial areas demonstrated limited digital literacy skills, particularly in accessing, evaluating, and utilizing digital learning resources to understand abstract biology concepts. This research aims to develop PowerPoint-based augmented reality media integrated with socio-scientific issues to enhance digital literacy. The study employed a Research and Development approach using the ADDIE model involving 19 students and one biology teacher at MA Arriyadlah Pandean, Probolinggo Regency. Data were collected through validation instruments, questionnaires, and pretest–posttest assessments, then were analyzed descriptively and inferentially using the Wilcoxon Signed-Rank Test due to the small sample size. The results showed that the media achieved very high validity (87.33%) and practicality (87.59%). Students’ digital literacy improved after implementation, indicated by a moderate N-Gain score (0.54) and significant differences between pretest and posttest scores. This study contributes an accessible AR-based biology learning medium integrated with socio-scientific issues to support digital literacy in pesantren-based education. The developed media were found to be feasible, practical, and potentially effective for contextual biology learning. However, the findings were limited to a small-scale implementation involving a single class and a single biology topic.